Pengembangan reka bentuk konsep menerusi kaedah penganalisaan fungsi - Shahrum Abdullah, (2001)
The main objective of this study is to discuss in detail an expansion of a conceptual design phase in a function analysis method. This paper contains an interaction between function analysis for design methodologies and conceptual design for total design process. In this case, the selected solution of the function analysis is a black box model. Within the scape, the main function of an engineering design problem is expanded and separated into several sub-functions and it is being done in the black box boundary. The detail stages of the black box methodology are described in the paper. The overall function analysis can be used by most of the design engineers in order to produce some creative ideas for the conceptual design, in which the idea generation is only referred as the sub-functions. The final part of this study is a creation of the black box model in designing the supporting equipment of the human's blood vessel using nickle-titanium alloy. As a medical term, this equipment is called an aortic stent